Influencing factors and knowledge gaps on anemia prevention among female students in Indonesia - Lafi Munira; Pramon Viwattanakulvanid (International Journal of Evaluation and Research in Education (IJERE), 2021)
Adolescents (10-19 years old) are at high risk of developing iron deficiency anemia. Prevalence of anemia in young women in Indonesia was 37.1% which increased to 48.9% in 2018, with the proportion of anemia in the age group of 15-24 years and 25-34 years. The objectives of this study were to understand the influencing factors and gaps of knowledge related anemia prevention among female high school students. A qualitative case study design was conducted (April-May 2020) among nine female students (15-18 years old) from two senior high schools in Banjarmasin, Indonesia. Sampling technique used in this study was purposive sampling. Registered student who has total study period in the school not less than six months and students who refused to participate in this study were excluded. Data collection was used focus group discussion via WhatsApp messenger video call. Data analysis was mixed between content analysis and thematic analysis. Female students admit that they lack the initiative to find out about anemia. With the lack of understanding about anemia, the female students admitted that they did not really know whether preventing anemia was an important thing to do. The anemia education program at schools needs to enhance the female student’s knowledge about iron tablet consumption.